Apparent Diffusion Coefficient as a Noninvasive Biomarker for the Early Response in Hepatocellular Carcinoma After Transcatheter Arterial Chemoembolization Using Drug-eluting Beads - Li, Basen; Zhou, Lei; Xu, Anhui; Li, Qin; Xiang, Huihua; Huang, Yanrong; Peng, Ling; Xiang, Kun; Zhang, Mingfeng; Wang, Nan (Current Medical Imaging, 2022)
Background: Prognostic evaluation for Hepatocellular Carcinoma (HCC) after Transcatheter Arterial Chemoembolization (TACE) using Drug-Eluting Beads (DEBs) is essential for guiding the personalized treatment and follow-up strategy. Apparent Diffusion Coefficient (ADC) has been reported as a biomarker in conventional TACE. Objective: This study aimed to evaluate the diagnostic value of ADCbaseline, ADC change, and ADCratio in predicting the early objective response for HCC after DEB-TACE. Methods: This prospective single-center study included 32 consecutive patients undergoing dynamic contrast-enhanced magnetic resonance imaging (MRI) and diffusion-weighted imaging before and 1 month after DEB-TACE. After DEB-TACE, patients were grouped based on the modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria into responders (complete response [CR], partial response [PR]) and nonresponders (stable disease [SD], progressive disease [PD]). The Mann– Whitney U test and receiver operating characteristic (ROC) curves were performed to assess the statistical differences in ADCbaseline, ADC change, and ADCratio between responders and nonresponders. Results: At post-DEB-TACE follow-up MRI, 62.5% (n = 20, 11 CRs, and 9 PRs) of patients showed objective response, and 37.5% (n = 12, 7 SDs, and 5 PDs) did not respond to chemoembolization. Nonresponders had a significantly higher ADCbaseline value than responders (p < 0.001). The ROC for identifying the response to chemoembolization demonstrated that the threshold ADCbaseline value of 0.920 × 10−3 mm2/s had 100% sensitivity and 70% specificity. The ADC change and ADCratio of responders were higher than that of nonresponders (p < 0.001). Conclusion: ADCbaseline, ADC change, and ADCratio may be utilized as a noninvasive biomarker for predicting the early response of HCC to DEB-TACE.
Keywords: diffusion-weighted imaging